Commerce House - Ghosh, Ayan (2023)
Commerce House is located on Currimbhoy Road. The first floor of the Commerce House hosts the contemporary art gallery Galerie Mirchandani + Steinruecke, representing some of the country’s most sought-after painters. The gallery opened in 2006.